Screening Biomarkers of Sudden Coronary Death Based on mRNA Expression Profile of Rat Myocardial Tissues - GUO Xiang-jie; LI Hao; BAI Ya-qin; WU Peng; ZHAO Chun-mei; DONG Yi-ming; CHEN Nian-nian; YUN Ke-ming; GAO Cai-rong (Fayixue Zazhi, 2022)
ObjectiveTo explore the differential expression of messenger RNA （mRNA） in myocardial tissues of rats with sudden coronary death （SCD）, and to provide ideas for the forensic identification of SCD.MethodsThe rat SCD model was established, and the transcriptome sequencing was performed by next-generation sequencing technology. Differentially expressed genes （DEGs） in myocardial tissues of SCD rats were screened by using the R package limma. A protein-protein interaction （PPI） network was constructed by using the STRING database and Cytoscape 3.8.2 on DEG, and hub genes were screened based on cytoHubba plug-in. Finally, the R package clusterProfiler was used to analyze the biological function and signal pathway enrichment of the selected DEG.ResultsA total of 177 DEGs were associated with SCD and were mainly involved in the renin-angiotensin system and PI3K-Akt signaling pathway. The genes including angiotensinogen （AGT）, complement component 4a （C4a）, Fos proto-oncogene （FOS） and others played key roles in the development of SCD.ConclusionGenes such as AGT, C4a, FOS and other genes are expected to be potential biomarkers for forensic identification of SCD. The study based on mRNA expression profile can provide a reference for forensic identification of SCD.